2009
DOI: 10.1590/s0100-879x2009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in parents of a Brazilian non-clinical sample of attention-deficit/ hyperactivity disorder (ADHD) students

Abstract: Higher prevalence rates of anxiety and depression have been reported in parents of children with attention-deficit/hyperactivity disorder (ADHD). The interaction between the burden of ADHD in offspring, a higher prevalence rate of this highly inherited disorder in parents, and comorbidities may explain this finding. Our objective was to investigate levels of ADHD, anxious and depressive symptomatology, and their relationship in parents of ADHD children from a non-clinical sample using a dimensional approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
3
9
1
2
Order By: Relevance
“…These results corroborate data from earlier studies examining parental psychopathology of children with ADHD (Barkley et al., , ; Befera & Barkley, ; Biederman et al., ; Chronis et al., , ; Epstein et al., ; Faraone & Biederman, ; Gadow et al., ; Ghanizadeh et al., ; Goldstein et al., ; Margari et al., ; Psychogiou et al., ; Scahill et al., ; Segenreich et al., ; Steinhausen et al., ), while adding an important new dimension to the analysis. In most of the earlier studies, parents showed higher levels of ADHD symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results corroborate data from earlier studies examining parental psychopathology of children with ADHD (Barkley et al., , ; Befera & Barkley, ; Biederman et al., ; Chronis et al., , ; Epstein et al., ; Faraone & Biederman, ; Gadow et al., ; Ghanizadeh et al., ; Goldstein et al., ; Margari et al., ; Psychogiou et al., ; Scahill et al., ; Segenreich et al., ; Steinhausen et al., ), while adding an important new dimension to the analysis. In most of the earlier studies, parents showed higher levels of ADHD symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…ADHD, Attention-deficit/hyperactivity disorder; MSDP, maternal smoking during pregnancy v 2 , chi-square statistic; df, degrees of freedom. Goldstein et al, 2007;Margari et al, 2013;Psychogiou et al, 2007;Scahill et al, 1999;Segenreich et al, 2009;Steinhausen et al, 2013), while adding an important new dimension to the analysis. In most of the earlier studies, parents showed higher levels of ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another shortcoming of family studies in ADHD is the occurrence of disorders, which may mimic ADHD symptoms, such as, anxiety and depression-an aspect addressed by both DSM-IV and 5 in criterion E. Different research groups [14][15][16][17][18], including ours, have demonstrated high comorbidity rates with anxiety and depression, both in the offspring and in parents [19]. Family studies need to consider gender effects on the aggregation of symptoms, a phenomenon referred to as 'parent of origin effect' [20,21].…”
Section: Introductionmentioning
confidence: 88%
“…A study showed that mothers of children with ADHD+ODD/CD suffered from mood disorders, anxiety disorders, and dependence on stimulant/cocaine and fathers suffered from alcohol consumption [ 16 ]. Another report indicated that symptoms of anxiety and depression in mothers of children with ADHD were more prevalent [ 17 ]. In another study, it was reported that fathers suffered from psychiatric illness with higher frequency than mothers so that 87% of parents of ADHD children had a history of substance use disorder [ 7 ].…”
Section: Discussionmentioning
confidence: 99%